The Rise of China National Medicines: Strategy and Financial Analysis of Medical industry - Wang, Yueru; Yin, Jie (Transactions on Economics, Business and Management Research, 2024)
China’s ageing population is becoming increasingly severe, so the demand for social medical and health services is growing. This also means that the demand for pharmaceutical consumption is promoting the market expansion of pharmaceutical circulation. This phenomenon has also promoted the continuous development of China’s pharmaceutical circulation industry. China National Medicines is one of the largest and most comprehensive pharmaceutical and health industry groups in China and has made great contributions to China’s pharmaceutical industry. This paper focuses on the factors affecting the existing business and future development of China National Medicines. First, it adopts PESTEL’s non-financial analysis of China’s National Medicines. Then, the profitability and liquidity indicators are taken as the means of analysis in the financial indicators. Thus, the value of selecting China National Medicines as an investment object is determined. The research found that China National Medicines has a strong ability to make profits and pay debts and has a better performance than other companies in the same industry, and some of the company’s drugs have certain advantages in the Chinese market. Therefore, the company has a specific investment value for investors.